Noodleheads Fortress of Doom - Arnold, Tedd; Hamilton, Martha; Weiss, Mitch, 1951- (Arnold, Tedd. Noodleheads, 2019)
Using knowledge from a library book, brothers Mac and Mac build a fortress but Meatball, armed with a book of his own, wants to take it from them.